A REVIEW OF THE SO-CALLED -BE/-BA PAST TENSES OF ZULU - Posthumus, L. C. (South African Journal of African Languages, 1982)
The aim of this paper is to give a semantic explanation of the verb groups with -be/-ba as a deficient verb stem and to account for elision within the deficient verb groups. The different types of complements will also be discussed. Having studied the findings of several grammarians on the so-called compound tenses of the African languages, it has become evident that they more or less have the same view of these verb forms in question. To them these forms constitute past tenses. Elision has been indicated but not exhaustively discussed. To them the semantic notion par-exellence is that of continuation of the action. As tense is a deictic category which relates the time of the action, event or state of affairs to the time of utterance, the forms containing -be/-ba as a deficient verb cannot be regarded as tense indicating. -be/-ba is used to indicate the shifting of the deictic centre from "now" to a new selected point in time. The deficient verb forms s/c + a + be, s/c + be, s/c + zo + ba/be and s/c + yo + ba/be respectively indicate the shifting of the deictic centre to long before coding time, shortly before coding time, shortly after coding time and long after coding time. Elision within the deficient verb groups which takes place in constituting the shortened form has been accounted for. Attention has also been given to the different types of complements of the -be/-ba deficient verb groups. There is apparently one instance where -be is not used only to indicate the shifting of the deictic centre, but also to indicate a mere past tense. This is the case when a non-inchoative copulative word group (in the past tense) is used as complement of -be.